GDPR v. GDPL: Strategic Adoption of the responsiveness approach in the elaboration of Brazil´’s General Data Protection Law and the EU General Data Protection Regulation - Iramina, Aline (Law, State and Telecommunications Review, 2020)
Purpose ”“ The main purpose of this article is to analyze the aspects of the responsiveness approach adopted by European and Brazilian lawmakers in the elaboration of data protection rules, such as GDPR and LGPD. Methodology ”“ The applied methodology is based on the responsive regulation theory and, additionally, the network governance theory, through the comparative analysis of personal data protection legal frameworks in Brazil and the EU. Findings ”“ Based on the comparative analysis of the GDPR and the LGPD, it is verified the adoption of escalated regulatory techniques of Ayres and Braithwaite’s enforcement pyramid in the developed of these norms, as a strategy adopted by lawmakers to guarantee a greater compliance from regulated entities.